An Analysis of the Trends in the Arena of Cooperation by the International Research Cooperation Related Experts - Noh, Younghee; Ro, Ji Yoon; Kwak, Woojung (International Journal of Knowledge Content Development & Technology, 2021)
The International Research Cooperation Information Center has carried out a project to collect the DBs related to the international research cooperation information, and build an online service system. This study seeks to examine and understand the trends of international research cooperation by analyzing the data corresponding to the other international cooperation DBs such as symposium and seminar, which may be said to be the arena of cooperation by the international research cooperation related experts, among the international research cooperation information DBs collected by the International Research Cooperation Information Center. The other international cooperation DBs are divided into the international cooperation consortium, international cooperation symposium, international research cooperation seminar, international training program, international research cooperation workshop, and the international research cooperation equipment / facility. It seems that, based on the research results, it is necessary to hold international cooperation programs, seminars, and workshops, among others, with a focus on the themes to recover the trends of international cooperation as in the past, and recover from the pandemic situation. The results of this study may be utilized as the basic data for the researchers related to the international research cooperation, and furthermore, by analyzing various international research cooperation information DBs in a multi-faceted manner, the studies analyzing the research trends of international research cooperation by field, subject, and type may be conducted, and the facilitation of the international research cooperation in Korea is expected moving forward.